365ODurability of response with larotrectinib in adult and pediatric patients with TRK fusion cancer. (24th November 2019) - Hyman, D; Tan, D S W; van Tilburg, C; Albert, C; Geoerger, B; Farago, A; Laetsch, T; Kummar, S; Doz, F; Lassen, U; Dubois, S; McDermott, R; et al.
Abstract: Background: Genomic rearrangements involving neurotrophic tropomyosin receptor kinase 1, 2, or 3 (NTRK1/2/3) result in constitutively active tropomyosin receptor kinase (TRK) fusion proteins that are oncogenic drivers in multiple pediatric and adult cancers. Larotrectinib is a selective TRK inhibitor approved by the US Food and Drug Administration in 2018 for the treatment of TRK fusion cancer based on a primary analysis in 55 patients from 3 clinical trials [Drilon et al. NEJM 2018]. Here, we report median duration of response (DOR) data in the primary cohort and updated data in an expanded cohort of 159 patients with TRK fusion cancer treated with larotrectinib, with 153 (55 primary + 98 supplemental) evaluable for efficacy. Methods: Patients with TRK fusion cancer detected by local molecular profiling were treated with larotrectinib across 3 studies (NCT02122913, NCT02637687, NCT02576431). Disease status was assessed by investigators using RECIST 1.1. Data cut-off was February 19, 2019. Results: In the primary cohort of 55 patients with a median follow-up of 26 months, the median DOR in 44 patients with complete or partial responses was 35.2 months (95% CI 21.2–not evaluable [NE]), with 17 progression events and 27 responses ongoing (range 1.6–44 months). Median progression-free survival in the primary cohort was 25.8 months (95% CI 9.9–NE), with 27 patients having progressed. In the expanded combined dataset, the most common tumor types included soft tissue sarcoma (n = 36), infantile fibrosarcoma (n = 29), thyroid carcinoma (n = 26), salivary gland carcinoma (n = 21), and lung cancer (n = 12). Median age was 43 years, ranging from < 1 month to 84 years; 33% < 18 years. The overall response rate was 79% (95% CI 72–85), with complete responses in 16%. Adverse events were mostly grade 1–2; 13% of patients had a grade 3–4 event related to larotrectinib. Only one patient discontinued due to an adverse event related to larotrectinib. Conclusions: These data confirm the marked tissue-agnostic efficacy and long durability of response in patients with TRK fusion cancer treated with larotrectinib. Larotrectinib demonstrated a favorable long-term safety profile. Screening patients for NTRK gene fusions should be considered. Clinical trial identification: NCT02122913, NCT02637687, NCT02576431. Legal entity responsible for the study: Bayer. Funding: Bayer. Disclosure: F. Doz: Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: BMS; Advisory / Consultancy, Research grant / Funding (self): Celgene; Advisory / Consultancy: Bayer; Advisory / Consultancy: Loxo Oncology; Advisory / Consultancy: Servier. L. Mascarenhas: Speaker Bureau / Expert testimony: Bayer. J. Berlin: Research grant / Funding (institution): PsiOxus; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): Symphogen; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Immunomedics; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): AbbVie (pharamcyclics); Research grant / Funding (institution): Boston Biomedical; Research grant / Funding (institution): FivePrime; Research grant / Funding (institution): Loxo; Research grant / Funding (institution): Incyte; Research grant / Funding (institution): Macrogenics; Honoraria (self): Nestle; Advisory / Consultancy: Rafeal; Advisory / Consultancy: Seattle Genetics; Honoraria (self): Eisai; Advisory / Consultancy: Taiho; Advisory / Consultancy: Armo. All other authors have declared no conflicts of interest.